Transient analysis with coupled field-circuit model and experimental assessment of a PMSG used in small-scale wind turbine for water heating purpose - Cetinceviz, Yucel; Sehirli, Erdal; Uygun, Durmus; Ocak, Cemil; Demirel, Huseyin (Springer Science and Business Media LLC, 2019)
This paper introduces the detailed coupled field-circuit analysis including performance characteristics of a 4-kW in-running rotor permanent magnet synchronous generator (PMSG) used in rural-type small-scale wind turbines for water heating purpose. The content of the work consists of design, analysis, optimization, production and testing processes and validation studies. An integrated 2D electromagnetic field and circuit model are used in the design and analysis processes. The electrical machine design involves complex and time-consuming processes. This model provides comprehensive information on machine behavior under different conditions and is an effective to demonstrate compliance with real load conditions prior to the manufacture. The goal of the optimization process is to find a design that offers cost, manufacturability and efficiency as well as generator output values. For this, a multiobjective optimization approach has been used. Typical design and simulation principles are applied to the designed PMSG, respectively, including calculation and evaluation of various output parameters for different simulated wind speed rates and varying load conditions. Furthermore, the analytical studies related to finite element methods and parametric approaches are presented in collaboration with experimental studies carried out for different load rates.
Keywords: Finite element method; Coupled circuit model; Prototype; Permanent magnet synchronous generator; 7. Clean energy